Cardiovascular Imaging: New Tools, Professional Imperatives - Douglas, Pamela S. (MD Conference Express, 2006)
Pamela S. Douglas, MD, President of the American College of Cardiology, and Chief, Cardiovascular Medicine, Duke University, launched the 55th Annual Scientific Session of the American College of Cardiology with a Presidential Address titled “Improving Imaging: Our Professional Imperative.”